Physical-chemical properties of Corema album (white crowberry or camarinha) - Andrade, Sónia (2015)
This study evaluated the biometric characteristics (diameter, mass), the chemical properties (moisture content, ﬁber, total and reducing sugars, total soluble solids, total acidity), and some physical properties (color, texture). The results obtained showed that the Corema album berries had an average diameter of 8.63 ± 0.84 mm, and a mass of 0.66 ± 0.11 g. Regarding the chemical analysis, the results obtained show an average moisture content of 87.89 ± 4.01 % (fresh weight) and a ﬁber content of 36.52 ± 1.96 % (dry matter). The percentage of total and reducing sugars was 62.80 ± 0.77 % and 41.24 ± 1.74 % (dry matter), respectively. The result also showed Brixº of 6.20 ± 0.03 and a total acidity of 10.7 ± 0.1 % (Citric Acid). This study allowed concluding that the berries Corema album at study showed parameters of diameter and mass higher than those reported in the bibliography. It was also possible to conclude through the chemical analyzes performed that these berries are a very rich source of water, ﬁbers and total sugars. Finally , these results conﬁrm that Corema album berries have multiple physical-chemical properties that may be of high interest to the market of commercial berries.